Carcinogenicity of perfluorooctanoic acid and perfluorooctanesulfonic acid - Zahm, Shelia; Bonde, Jens Peter; Chiu, Weihsueh A; Hoppin, Jane; Kanno, Jun; Abdallah, Mohamed; Blystone, Chad R; Calkins, Miriam M; Dong, Guang-Hui; Dorman, David C; Fry, Rebecca; Guo, Huan; et al. (The lancet oncology, 2024)
Applications for fluoropolymers and PFOA include surface coatings for stain, oil, and water resistance on household products, carpets, textiles, and food packaging; personal care products; seals; coatings for cables and wires; and construction materials. Since the previous classification of PFOA (as “possibly carcinogenic to humans”, Group 2B) by the IARC Monographs in 2014,2 many new studies have investigated the association between exposure to PFOA and cancer in experimental animals and humans, as well as mechanistic endpoints relevant to the key characteristics of carcinogens. [...]PFOA induces oxidative stress, modulates receptor-mediated effects (via PPARα, CAR/PXR, and PPARγ), and alters cell proliferation, cell death, and nutrient and energy supply in human primary cells and experimental systems. For testicular cancer, additional evidence was a positive association in an ecological analysis conducted by the Working Group of available data on orchiectomies from the Veneto region of Italy, and a US study finding no associations.9 For all other cancers, the evidence was “inadequate”, as there were only sporadic positive findings.